Weltanschauung and the Manifestation of Beliefs in the Ethnic Traditions of Sarawak: (Weltanschauung dan Manifestasi Kepercayaan Tradisi Etnik di Sarawak) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2013)
The Weltanschauung and traditional beliefs of ethnic groups in Sarawak, such as the Melanau, Iban and Kedayans is important in their daily life. Their world view is influenced by animistic beliefs that have existed since before the arrival of Islam and Christianity, in which a belief in spirits and the soul is fundamental. The objective of this study is to examine the world view and manifestations of this belief in the traditions of these ethnic communities, as evident through certain ceremonies. This study combines ethnographic approaches and library research. This study has found that even after the arrival of Islam and Christianity, animism is still enshrined in the collective memory of these communities. The Collective memory is thus a part of the cultural heritage of ethnic groups in Sarawak. The Melanau Likow still practise this belief, as well as the Iban, especially those in rural areas, where the practices are more specifically linked to agriculture and festivities. The Makan Tahun ceremony of the Kedayan ethnic group, on the other hand, has undergone a process of islamization in order to suit the new religious beliefs of the Kedayans. Clearly, the dynamics of culture influence world view and modify the manifestation of traditions, which is the main significance of these findings.Keywords: ethnic beliefs, world view, tradition, Sarawak